Cabin1 localizes in glomerular podocyte and undergoes nuclear translocation during podocyte injury. (14th September 2015) - Wen, Yueqiang; Wang, Zebin; Liu, Lingling; Zhang, Yajie; Zhou, Peilan; Liang, Jianbo
Abstract: Context : Podocyte injury is related to increasing proteinuria and contributes to the progression of kidney disease. Calcineurin binding protein 1 (Cabin1) is a repressor of myocyte enhancer factor 2 (MEF2) and calcineurin-mediated transcription in the immune system. Moreover, Cabin1 interacts with p53 and negatively regulates p53 in tumor cells. However, its function in kidney is unknown. Objective : To explore the exact localization of Cabin1 in glomeruli, as well as the relationship between Cabin1 and podocyte injury. Methods : Sprague–Dawley rats were sacrificed to observe the localization and protein expression of Cabin1 in the kidney. Cabin1 localization and protein expression were detected by immunofluorescence staining and western blot, respectively. Mouse podocytes were cultivated at 33 °C to propagate, then cells were transferred to an incubator at 37 °C to allow differentiation. Differentiated podocytes were stimulated by angiotensin II (AngII) or AngII plus tacrolimus. Cells were harvested to detect the localization and protein expression of Cabin1. Cytoplasmic and nuclear protein were separated by protein extraction kit. Results : Cabin1 mainly localized in the nuclei of glomerular innate cells, it colocalized with WT-1 in podocytes nuclei. Western bolt showed Cabin1 protein remarkably expressed in renal cortex. AngII-induced Cabin1 nuclear protein significantly increased, accompanied by cytoskeleton disruption in cultured mouse podocytes. Conclusion : Cabin1 localizes in glomerular podocytes. AngII induces nuclear translocation of Cabin1 in cultured podocytes.